Association of Cigarette Smoking with Hearing Loss in Young Male Adults of Hyderabad, Pakistan - Shaikh, Shakil Ahmed; Laghari, Zulfiqar Ali; Memon, Salma Farrukh; Bhatti, Muhammad Ali (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To evaluate the effects of cigarettes smoking on hearing loss in young adult’s aged < 35 years. METHODOLOGY: This cross-sectional research was carried out in the ENT department of Combined Military Hospital Hyderabad. The hearing loss was assessed by Audiometry, Whisper test, Rinne's test and Webbers test. The young healthy adults with no known history of exposure to extreme noise were included. All the participants which had any type of infections or any otic injury were excluded from study. The audiometry was performed on the audiometer MAICO-MA39 (Berlin Germany) at Combined Military Hospital Hyderabad. RESULTS: In this study, 148 apparently healthy participants were selected, out of 148, 73 were smokers and 75 were nonsmokers. The age of the participants ranged between 20 to 35 years with the mean age of smokers 28.99±3.731, and nonsmokers 28.00±4.451 non-smokers. The data collected indicate significantly higher prevalence of hearing loss in smokers 49.31%, P < 0.01 than in non-smokers (30.66%). Age of smokers was positively correlated (r = 0.427, P < 0.01) with hearing loss. Frequency of cigarettes smoked per day was positively correlated (r=0.715, P < 0.01) and year of smoking was also positively correlated with hearing loss (r = 0.620). The correlation of frequency of cigarette smoking and duration of smoking with hearing level was extremely significant (P < 0.01). CONCLUSION: These findings suggest that cigarette smoking is associated with hearing loss in young adults; this study will be helpful in making public health policies.